A Hydraulic Performance Model of Khassa Chai River under Varying Flow Conditions - Mahmood, Khalid M.; Mohammed-Ali, Wesam S. (Engineering, Technology & Applied Science Research, 2025)
The increasing deterioration of rivers highlights the need for effective restoration mechanisms and flow management strategies to sustain the local ecosystems. This study evaluates the hydraulic performance of rivers under varying flow conditions using the Hydraulic Engineering Center-River Analysis System (HEC-RAS) model, with the Khassa Chai River as a case study. A Differential Global Positioning System (DGPS) survey was conducted along a 14 km distance, capturing 73 cross-sections of the river. The model results indicate that several reaches are at risk of flooding, revealing the need for river restoration to ensure that the cross-sections can accommodate the design discharge (1200 m³/s). These findings emphasize the importance of sediment removal and channel maintenance to enhance the river’s hydraulic capacity.